Effectiveness of a smartphone-based worry-reduction training for stress reduction: A randomized-controlled trial. Issue 9 (2nd September 2018) - Versluis, Anke; Verkuil, Bart; Spinhoven, Philip; F Brosschot, Jos
Abstract : Objective: Perseverative cognition (e.g. worry) and unconscious stress are suggested to be important mediators in the relation between stressors and physiological health. We examined whether a smartphone-based worry-reduction training improved a physiological marker of stress (i.e. increased heart rate variability [HRV]) and unconscious stress. Design: Randomised-controlled trial was conducted with individuals reporting work stress ( n = 136). Participants were randomised to the experimental, control or waitlist condition (resp. EC, CC, WL). The EC and CC registered emotions five times daily for four weeks. The EC additionally received a worry-reduction training with mindfulness exercises. Main Outcome Measures: Primary outcome was 24-h assessments of HRV measured at pre-, mid- and post-intervention. Secondary outcomes were implicit affect and stress. Effects on heart rate and other psychological outcomes were explored. Results: A total of 118 participants completed the study. No change from pre- to post-intervention was observed for the primary or secondary outcomes. The change over time was not different between conditions. Conclusion: Findings suggest that the training was ineffective for improving HRV or psychological stress. Future studies may focus on alternative smartphone-based stress interventions, as stress levels are high in society. There is need for easy interventions and smartphones offer possibilities for this.